Download presentation

Presentation is loading. Please wait.

Published byConor Murrell Modified over 2 years ago

1
Your Transformation Equation y = - a f(-( x ± h)) ± k - a = x-axis reflection a > 1 = vertical stretch 0 < a < 1 = vertical compression -x = y-axis reflection + h = horiz shift left - h = horiz shift right + k = vert shift upward - k = vert shift downward

2
Your Transformation Equation y = - a f(-( x ± h)) ± k - a = x-axis reflection a > 1 = vertical stretch 0 < a < 1 = vertical compression -x = y-axis reflection + h = horiz shift left - h = horiz shift right + k = vert shift upward - k = vert shift downward

3
Your Transformation Equation y = - a f(-( x ± h)) ± k - a = x-axis reflection a > 1 = vertical stretch 0 < a < 1 = vertical compression -x = y-axis reflection + h = horiz shift left - h = horiz shift right + k = vert shift upward - k = vert shift downward

4
Your Transformation Equation y = - a f(-( x ± h)) ± k - a = x-axis reflection a > 1 = vertical stretch 0 < a < 1 = vertical compression -x = y-axis reflection + h = horiz shift left - h = horiz shift right + k = vert shift upward - k = vert shift downward

Similar presentations

© 2017 SlidePlayer.com Inc.

All rights reserved.

Ads by Google